DIGITAL LINGUISTICS IN ENGLISH LANGUAGE TEACHING. - Uljayeva Shahzoda Turdalievna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores the impact of digital linguistics on English language teaching (ELT) in the internet age. It discusses lexical, syntactic, pragmatic, and discourse changes driven by digital communication technologies and examines how these changes influence teaching practices. The paper highlights the role of digital tools in ELT, the need for teacher digital literacy, and future directions such as multimodality and the integration of artificial intelligence in language education.